2011
DOI: 10.1007/s12046-011-0005-9
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis in a functionally graded disc under mechanical loads and a steady state temperature distribution

Abstract: An analytical thermoelasticity solution for a disc made of functionally graded materials (FGMs) is presented. Infinitesimal deformation theory of elasticity and power law distribution for functional gradation are used in the solution procedure. Some relative results for the stress and displacement components along the radius are presented due to internal pressure, external pressure, centrifugal force and steady state temperature. From the results, it is found that the grading indexes play an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…In another study by Callioglu; It is concluded that the displacement of a disc on the outer surface is greater than the displacement on the inner surface. Similar results emerged in this study; It has been observed that the radial displacement on the inner surface of the disc is less than the displacement on the outer surface of the disc [36]. In a different study by Ondurucu and Kayıran; radial, tangential stresses and displacements in the radial direction were investigated numerically for the bimaterial disc exposed to linear decreasing temperature.…”
Section: Disc Nosupporting
confidence: 86%
“…In another study by Callioglu; It is concluded that the displacement of a disc on the outer surface is greater than the displacement on the inner surface. Similar results emerged in this study; It has been observed that the radial displacement on the inner surface of the disc is less than the displacement on the outer surface of the disc [36]. In a different study by Ondurucu and Kayıran; radial, tangential stresses and displacements in the radial direction were investigated numerically for the bimaterial disc exposed to linear decreasing temperature.…”
Section: Disc Nosupporting
confidence: 86%
“…Kordkheili and Naghdabadi (2007) presented a solution for thermo-elasticity in hollow and solid rotating functionally graded disks. Exact solutions for stresses in functionally graded annular discs rotating at a constant angular velocity under temperature loading (Bayat et al, 2009;Çallıoğlu, 2011;Çallıoğlu et al, 2011;You et al, 2007) are also found in literature. Bektaş and Akça, (2012) conducted analytical and numerical analysis of FG disc using power law functions.…”
Section: Introductionmentioning
confidence: 88%
“…Kim and Paulino [16] evaluated the mixed-mode fracture parameters in FGMs using FEM. The analysis of FGM coatings was performed in many works by computational methods, usually FEM, or analytical tools [10,[17][18][19][20]. Some other approaches to simplify the mechanics of FGMs were developed like using equivalent eigenstrain and distributed dislocation technique to symbolize the cracks by Afsar and Song [21].…”
Section: Fracture In Fgmsmentioning
confidence: 99%